Unravelling EFL teachers’ mastery of TPACK to promote students’ participation - Joko Prayudha.S; Ami Pradana (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
Technology plays a significant role in the development of students, especially in building their interest in learning and understanding a material. Further, this can be an entertainment medium and a communication tool between a teacher and students. Therefore, this study aims to explain the benefits of using technology in learning English and enhance active learning participation. The method used in this research is qualitative through a descriptive approach. Data were obtained through classroom observation and interviews to obtain data in the form of opinions regarding the use of integrated TPACK in increasing student participation in learning. Data were analyzed through three stages, i.e., reduction, display, and conclusion. The study results show that the teachers applied a variety of innovative and diverse learning media through the integration of TPACK used in the classroom. By providing this technology assistance like TPACK learning, convenience, excitement, and engagement could be created during the class. Moreover, this study also reported that by choosing the proper technology application based on students’ characteristics, students could participate more actively and more creatively which could support the learning atmosphere, build a sense of comfort in learning, and enhance the learning participation.